Modelos deposicionais comparados dos reservatórios areníticos santonianos-campanianos da formação Calumbi, bacia Sergipe-Alagoas - Figueiredo, Muriel Nascimento de (2014)
The significance of the turbidites and the related deposits as oil/gas reservoirs in Brazil started in 1968, when the oil exploration began in the brazilian continental shelf, restating in 1985 and 1987 with the beginning of the exploration in deep and ultra-deep waters. The main objective of this dissertation is to contribute with new data and interpretations about the outcropping onshore portion of the Calumbi Formation, connecting the collected and interpreted data with the quality of the feasible reservoirs in the offshore of the Sergipe Sub-Basin. The Sergipe-Alagoas Basin is located in the northeastern part of the brazilian continental margin, being subdivided in 5 stages according to its tectono-sedimentary evolution: sineclisis, pre-rift, rift, post-rift, transitional and drift, the last one is related to the Calumbi Formation. The continental shelf and the deep waters are the prevailing depositional environments in the Calumbi Formation, being the shelf dominated by storms and waves and the deep waters dominated by gravity flows. In this study, 8 outcrops from the Campanian-Santonian section of the Calumbi Formation have been described, and so have been 11 thin sections, 6 representative of these outcrops and 5 from previous studies. The stratigraphical correlation between these outcrops, including also previously described outcrops and petrographical observations, have made possible to draw interesting conclusions about the shelf sands in bypass situation to the deep water turbidites. The described outcrops are part of a shelf environment which has dominated the proximal sedimentation of the Calumbi Formation on the Upper Cretaceous, from the Santonian to the Campanian